Mobilizing through dialogue: building interdisciplinary partnerships among forest health, wildland fire, and public health sectors to find solutions to address the impact of wildland fire smoke on communities. (16th March 2023) - D'Evelyn, SM; Blancas, M; Pollowitz, M; Haugo, RD; Masuda, YJ; Prichard, SJ; Ray, K; Walker, EG; Spector, JT
Abstract: The impact of smoke from wildland fires on communities across the western United States is an interdisciplinary crisis that requires an interdisciplinary solution. There are increasing calls for cross-collaboration between forest, fire, air quality, and public health practitioners to best prepare communities for ever-worsening smoke seasons. However, opportunities to engage interdisciplinary groups of practitioners and stakeholders on this topic have been largely missing. We report on the development and implementation of a hybrid in-person and online workshop that brought together practitioners from Washington State to foster new interdisciplinary relationships and partnerships in order to integrate public health considerations into forest management during and beyond fire season. This workshop highlighted ways in which hybrid workshops can facilitate discussions across traditionally siloed stakeholders to address the community health crisis of wildfire smoke and illuminate tangible steps for further facilitating integrated discussions around a shared area of interest. Key lessons included the importance of introductory meetings for establishing strong collaborations and the strength of hybrid settings for fuller participation by diverse stakeholders. This manuscript outlines ways in which local practitioners from other smoke-impacted communities can begin to build and utilize interdisciplinary partnerships to prepare and adapt for longer and more severe wildland fire smoke seasons.